Development and validation of a critical health literacy scale<subtitle>Exploring media literacy, social determinants, and empowerment</subtitle> - Mi Zhou; A. Susana Ramírez; Sandie Ha; Deepti Chittamuru; Yueqi Yan (Critical Public Health)
Critical health literacy has attracted much attention as an indicator of success beyond individual behavior change objectives in health promotion and as a tool to assess public health education. Despite its importance, there remains no consensus about how to operationalize critical health literacy. Building on Freire’s concepts of critical consciousness and empowerment, we conceptualize critical health literacy as comprising reflection (media literacy and awareness of social determinants) and action (psychological empowerment). We developed and validated an 18-item critical health literacy scale among young adult Latinas (N = 1,029) aged 18–29 years (mean age = 19.6). The scale measures three dimensions: media literacy, awareness of social determinants of health, and psychological empowerment. Face and content validity were established through focus groups and expert panel reviews. We used exploratory factor analysis (EFA) on half the sample to identify the dimensional structure, followed by confirmatory factor analysis (CFA) on the remaining half to assess convergent and discriminant validity. The EFA and CFA confirmed a five-factor structure with acceptable fit indices (TLI = .96, CFI = .95, RMSEA = .04, SRMR = .03). The scale demonstrated high internal consistency and composite reliability. Convergent and discriminant validity were established for most subscales, with the community control subscale showing weaker but theoretically important psychometric properties. The validated critical health literacy scale provides a reliable tool for assessing understanding of social and commercial determinants of health and the degree to which young people feel empowered to engage in social change. This instrument can be used to assess multiple levels of intervention effects consistent with a socio-ecological model of health.